PROSPECT THEORY DAN HUBUNGAN ANTARA RISK DAN RETURN : STUDI EMPIRIS DI INDONESIA - , raymond ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study aimed to examine the prospect theory and the relationship between risk and return be reviewed of return which is above target level and returns below target level in the financial industry and entire industry listed in Indonesia Stock Exchange (IDX). In this study the dependent variable (risk) used variance of Return on Assets (ROA) and variance of return on equity (ROE) and for the independent variables (return) used ROA and ROE. The sampling technique used in this research is purposive sampling. The samples used were all companies listed in Stock Exchange 2008-2012 period. To examine the relationship between risk and return then it will use technique of multiple linear regression analysis. The results of this study found that there is a significant negative relationship between risk and return for return above target level and there is a significant positive relationship between risk and return for return below target level and overall in this study accordance with the Prospect Theory proposed by Kahneman and Tversky.